A reconsideration of the empusellous species of Specklinia (Orchidaceae: Pleurothallidinae) in Costa Rica - Pupulin, Franco; Karremans, Adam P.; Gravendeel, Barbara (Phytotaxa, 2012)
This paper focuses on the systematics of the Specklinia endotrachys species complex in Costa Rica. Traditionally considered a variable species, S. endotrachys is here treated as one of at least four, albeit closely related, taxa. Of these species, S. endotrachys, S. pfavii, and S. spectabilis are described and illustrated from living material, and S. remotiflora is described and illustrated as new to science. Specklinia remotiflora is compared with S. endotrachys and S. spectabilis, from which it differs in the repent habit, lax inflorescence and campanulate flowers provided with convergent sepals and non-apiculate petals. New combinations are proposed for Pleurothallis pfavii and P. spectabilis. A lectotype is selected for Pleurothallis endotrachys. Observations on the pollination of S. remotiflora and S. spectabilis in cultivation are given.